Interaksi Intelektual dan Kehendak dalam Pandangan John Calvin: Membangun Jembatan Antara Filsafat Pendidikan Calvin dan Freire - Tampubolon, Yohanes Hasiholan (STT Reformed Injili Internasional, 2025)
This article explores the interaction between intellect and will in education according to the thoughts of John Calvin, as well as its relevance to Paulo Freire's critical pedagogy. Calvin emphasizes the importance of balancing intellect and will in the pursuit of truth, which aligns with Freire’s principles that encourage students to think critically and reflectively. The process of contemplation in Calvin's thought, where individuals reflect on knowledge to influence their will, mirrors Freire's reflective approach in critical education. Furthermore, both emphasize the freedom in decision-making, where individuals should act based on true knowledge and moral values. Calvin's thoughts also highlight the importance of social transformation, in line with Freire's vision of creating individuals who are not only intellectually competent but also morally committed to improving society. This article employs qualitative research methods. The findings indicate that the thoughts of Calvin and Freire complement each other in shaping a framework for education that is critical and oriented towards social change.